A Software Framework for Simulating Stationkeeping of a Vessel in Discontinuous Ice - Ivan Metrikin (Modeling, Identification and Control, 2014)
This paper describes a numerical package for simulating stationkeeping operations of an offshore vessel in floating sea ice. The software has found broad usage in both academic and industrial projects related to design and operations of floating structures in the Arctic. Interactions with both intact and broken ice conditions can be simulated by the numerical tool, but the main emphasis is placed on modelling managed ice environments relevant for prospective petroleum industry operations in the Arctic. The paper gives a thorough description of the numerical tool from both theoretical and software implementation perspectives. Structural meshing, ice field generation, multibody modelling and ice breaking aspects of the model are presented and discussed. Finally, the main assumptions and limitations of the computational techniques are elucidated and further work directions are suggested.